2014
DOI: 10.2105/ajph.2014.302153
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Effects of Nonlifesaving Early-Stage Breast Cancer Detection on Mammography Rates

Abstract: We estimated the effect of anecdotes of early-stage, screen-detected cancer for which screening was not lifesaving on the demand for mammography. We constructed an agent-based model of mammography decisions, in which 10|000 agents that represent women aged 40 to 100 were linked together on a social network, which was parameterized with a survey of 716 women conducted through the RAND American Life Panel. Our model represents a population in equilibrium, with demographics reflecting the current US population ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…One of the most important determinants of the dynamics that the model exhibits is whether each behavior, and , tends to lead to experiences that support the same behavior, or whether they lead to experiences that support switching behaviors. While the models described below are fairly stylized and are, for the most part, simpler than models we would develop for a particular problem (Nowak and Parker, 2014), they can begin to realistically capture the essential dynamics for representative classes of behaviors.…”
Section: Results From Our General Abmmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most important determinants of the dynamics that the model exhibits is whether each behavior, and , tends to lead to experiences that support the same behavior, or whether they lead to experiences that support switching behaviors. While the models described below are fairly stylized and are, for the most part, simpler than models we would develop for a particular problem (Nowak and Parker, 2014), they can begin to realistically capture the essential dynamics for representative classes of behaviors.…”
Section: Results From Our General Abmmentioning
confidence: 99%
“…In other cases, combined information about a behavior and outcome is likely to be transmitted together (Box H). In prior work, we found that most of the time, when women learn about breast cancer diagnoses of others they know, they are aware both of the screening behaviors and prognoses of the women diagnosed (Nowak and Parker, 2014). Finally, sometimes an outcome is more observable than a behavior; for example, if an individual overeats when alone, the likely resulting overweight and obesity are highly observable, whereas the health behavior is not (Box I).…”
Section: Information Is Transmitted In the Social Networkmentioning
confidence: 99%
See 3 more Smart Citations